IJCM_408A: Knowledge and perception of female feticide among medical students - Darshan B B; Pahuja Mayank; Harshwardhan; Jaiswal Sukriti; Shukla Tanya (Wolters Kluwer Medknow Publications, 2024)
Background: The preference for male children over female children has resulted in a declining sex ratio. We need to tackle and treat the mindset of people who don't value the existence of females and consider them a burden. Objectives: To study the knowledge and perceptions related to female feticide among medical students of Mangalore. Methodology: A questionnaire-based cross-sectional study was carried out among third and fourth year MBBS students of Kasturba Medical College, Mangalore. A sample size of 300 was calculated and they were selected into the study using Convenient Sampling. Data were entered and analyzed by using SPSS version 29. Results: Around 94.6 % of the participants were aware of the correct meaning of the term "Female feticide". Almost, 94.3 % of the participants had an awareness about the practice of female feticide being prevalent in India. Nearly 74% of participants received information about female feticide from multiple media sources and 51.1 % from Newspapers. Conclusion: The study shows medical students have the optimum level of awareness about the factors of female feticide. They favoured that the decline in sex ratio is the main impact of female feticide.